Revisiting Femvertising - Analysing through Multimodal Discourse Analysis - Chithra, S. Aswini (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The depiction of Women in advertising gained considerable academic attention, fuelled by the feminist movements and progression of women’s role in society. Early studies reported the depiction of women stereotyped with domestic work, dependent to men and sexually objectified grounding with gender roles. In 2015, SheKnows Media, a digital lifestylecompany introduced the term Femvertising Awards to feature brands who break down the gender stereotypes by empowering women in advertising campaigns. This paper intends to examine the impression of Femvertisingon the representation of women in relation with Feminism as a growing social movement and social responsibility of brand in advertising. The study investigates through Multimodal discourse analysis in terms of representation, interactive and compositional whole.